“Mercedes-Benz” Sign in Posttraumatic Falcotentorial Subarachnoid Hemorrhage - Bansal, Sumit; Mahapatra, Ashok Kumar (Indian Journal of Neurotrauma, 2015)
Two-wheeler riders have a disproportionately higher incidence of traumatic brain injuries (TBI) as compared with other modes of transport. Diagnosis of posttraumatic falcotentorial subarachnoid hemorrhage can be made from CT scan. With such findings on CT scan, the authors are proposing a new sign named as “Mercedes-Benz” sign to identify such type of hemorrhage.
Keywords: head injury; falcotentorial subarachnoid hemorrhage; CT scan